Report of the naspe policy conference on antibradycardia pacemaker follow-up: effectiveness, needs, and resources. - Bernstein AD; Irwin ME; Parsonnet V; Wilkoff BL; Black WR; Buckingham TA; Maloney JD; Reynolds DD; Saksena S; Singer I; Nickelson DE; Schurig L (Pacing & Clinical Electrophysiology, 1994)
On May 4-5, 1993, a policy conference was held in San Diego, California, under the sponsorship of the North American Society of Pacing and Electrophysiology (NASPE) to identify the fundamental goals of antibradycardia pacemaker follow-up, evaluate the effectiveness with which it achieves those goals, and formulate specific recommendations as to how it can be made more effective. The conference addressed clinical, administrative, and educational objectives, focusing on existing and potential resources for follow-up testing and the appropriate frequency of their application. The training of physicians and associated professionals engaged in follow-up also was addressed, as were regulatory and reimbursement issues. This report summarizes the conclusions and recommendations arrived at during the conference and subsequently approved by the NASPE Board of Trustees.